Two additional new species of Clypeocaenis Soldán, 1978 (Ephemeroptera: Caenidae) from the Western Ghats of Peninsular India - Balasubramanian, Chelliah; Muthukatturaja, Marimuthu (Zootaxa, 2021)
Two new mayfly species of Clypeocaenis (Ephemeroptera: Caenidae) are described based on nymphal and adult characters from Kaveri River, Kodagu, Karnataka, Southern India. The main characteristics that distinguish Clypeocaenis kaveri sp. nov. from other Oriental species are: (i) fore femur with 4 long spines at middle of inner margin, a row of bifid spines at outer margin and row of bifid spines at subapical surface; (ii) dorsal surface of femora with complete transverse row of bifid setae located 3/4 distance from the base; (iii) forceps smaller than penis lobe. The main characteristics that distinguish Clypeocaenis napoklu sp. nov. from other Oriental species are: (i) fore femur with 2 long spines at middle of inner margin and row of thin setae on outer margin; segment 2 with bifid spine at apex.(ii) dorsal surface of femora with incomplete transverse row of bifid setae located 2/3 distance from the base; (iii) forceps little longer than penis lobe. A key for the nymphs of described species has been provided.